Acceptance of google classroom for learning English exit test / Tuan Sarifah Aini Syed Ahmad, Zarina Suriya Ramlan and Shashi Kumar Krishnan - Syed Ahmad, Tuan Sarifah Aini; Ramlan, Zarina Suriya; Krishnan, Shashi Kumar (Universiti Teknologi MARA, 2020)
Online learning has been implemented at the tertiary level by using many platforms such as the university learning management system, massive open online courses (MOOCs) and mobile applications. Online learning permits personalization and autonomous learning. However, this is not the case for the English Exit Test. An initiative was made to provide an online platform for students to practice using the language via Google Classroom. Google Classroom can be accessed as a mobile application on a smartphone or on the web by using a computer. It is essential to support the students' learning in preparation for the test since it is the requirement of graduation for degree students at Universiti Teknologi MARA. This study aimed at determining the level of acceptance in using Google Classroom for learning English Exit Test among students. The sample was selected using purposive sampling. The data were collected using a survey designed based on the Technology Acceptance Model (TAM) and went through data cleansing using Statistical Packages for the Social Sciences (SPSS) Version 21. The data were then analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that students positively accepted the use of Google Classroom in preparation for the English Exit Test.